INOVASI PEMBUATAN REBAB VERSI RAHARJA: KAJIAN ORGANOLOGI DAN AKUSTIKA - Donovan Hardy; Bayu Wijayanto; Setya Rahdiyatmi Kurnia Jati Linuar (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This research began with the phenomenon of making rebab initiated by Raharja (hereinafter referred to as rebab Raharja). This produk is a realization of the stimulus of the idea of ​​developing musical instruments in 1993, when he studed at ISI Yogyakarta. The idea of ​​creating rebab Raharja was motivated by the emergence of contradictory criticism of the use of conventional rebab in the presentation of Raharja's gamelan in 1993. There are several parts of his musical composition that have a hard nuance and the presentation of the rebab is done in a standing position. Anticipatory efforts were carried out creatively by taking a number of innovative steps. The goal is that the new rebab details can be used in the context of presenting contemporary musical works. The process of making and experimenting with making rebab Raharja has taken place three times, that was in 1994, 2010, and 2023. Each stage produces two products that have differences in physical and non-physical aspects. The purpose of this study was to examine and describe Raharja's innovation. The realization of his ideas has been carried out in several aspects, such as: technology of making the rebab’s body with resin as an alternative material to replace wood, the design of the shape and construction of the rebab, and the application of electrical technology products as sound generating devices. The method applied in this study is qualitative descriptive analysis. The method and nature of the research are applied to analyze and describe the innovation and process of making Raharja’s rebab. The physical aspect is studied using the discipline of organology, while the sound quality and its processing are carried out using acoustics, a branch of physics that discusses sound. The results obtained from this study are in the form of a description of the meaning of innovation, forms of innovation, knowledge of materials, making design shapes and construction, the process of making the rebab’s body and the process of producing sound by applying electrical technology products. The realization of this idea, changing the physical appearance and sound quality can be processed to be more diverse. As far as the author knows, there has been no rebab made like Raharja's idea. The innovation that has been carried out has the opportunity to be applied to other details, either with the same or different thinking. In essence, it has a noble goal to develop and globalize gamelan through the development of its musical instruments, so that it has a functional suitability and technological equality with other musical instruments.